(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Background: Blood transfusion is a life saving intervention in some obstetric and gynecological cases but is associated with risk of transfusion reaction and transmission of infection . Appropriate use of blood and blood products is of utmost importance for the safety of the patients. During the evaluation of an ongoing study on PPH,it appears that rate of blood transfusion is unexpectedly high in this centre, which raised the inquisitiveness in evaluating the rate and rationality of blood transfusion in present practice. Objective : To determine the incidence of blood transfusion in admitted and operated cases and is also to evaluate the indication of transfusion among the study patients. Subject and Method: It was an observational descriptive study, conducted from 1st April 2012 to 30th June 2012 in department of obstetrics and gynecology of Ad-din Women Medical College Hospital , Dhaka . Total 256 cases were included for the study, who received blood and /or blood products during the study period. Results: Transfusion rate in total admitted patients was 9.23% . Most common indication for blood transfusion in obstetric patients was mild preoperative anaemia with or without excessive bleeding during cesarean section (63.92%) and second common cause was antenatal anaemia (24.05%). In gynecological cases abortion (45.91%) was the commonest indication for blood transfusion and next common conditions were total abdominal hysterectomy (20.40%),vaginal hysterectomy (7.14%), ectopic pregnancy and post coital tear (6.12%) and( 6.12%). Conclusion: In this study it was observed that, blood transfusion was not appropriate in all cases, specially in cases where single unit blood was transfused . So creation of awareness among the junior doctors, obstetricians, nurses midwives is essential by developing regular education and training programme. J Bangladesh Coll Phys Surg 2016; 34(1): 9-14